Weavers, embroiderers, and armadoras in Yucatan: New and old work classes at home - Jimena Méndez-Navarro; María de Jesús Ávila-Sánchez (Íconos)
Work from home is one of the traditional forms of textile production that is still present in diverse regions of the world. The new local expressions connected to tourism have been able to position their products at a global scale. Also, in countries with cultural diversity there are regional markets where the population uses traditional clothing in their day-to-day life. This article offers a conceptual understanding of the novohispano proto-industry and the work activities at home. The case of an area of Southern Mexico is presented, the type of work that has been produced through textile activity, as well as its geographical specialization. The point of view of weavers, embroiderers, and armadoras in 13 municipalities of Yucatan is examined. Through interviews it was possible to recompile the details of their activity, the commercial connections, the means and ways in which this work is developed. This research is complemented by analyzing the longitudinal data of surveys about work from home, narrowing down on the textile economic sector. The findings suggest there are a set of factors connected to the proto-industry theory, specifically the relationship between the urban and rural, the extraterritorial market that strengthens the labor relationship between works and the commercial capital in the economic expansion of the state of Yucatan, Mexico.